Um pássaro invocou mudamente o abismo: tensão entre as categorias positivas e negativas na poética de Orides Fontela - Batista, Jaqueline de Carvalho Valverde [UNESP] (2015)
The aim of this work is to study the poems Destruição, Meio-dia, Caramujo, Aurora, Gênesis, Ver, Noite, Prece, Vésper, Pouso Ode, Ode I, Nudez and Meada, by Orides Fontela's Poesia Reunida [1969-1996] (2006), because, in this corpus in which the metalinguistic reflection is extreme, the tension relation - between the negative categories (such as incommunicability, darkness, hermeticism, destructive flashes, which can be found in the images of death, abyss, silence, murder and blood) and the positive categories (such as clearness, lightness and freedom) - acts as a resistance force of the poetry itself, despite language limits. The tension relation, along with the fragmentation, the blank spaces and the circularity, builds the symbolic death of the word which cannot say everything and, because of this, silences itself in order to mean more and transcend in new experiences. In this master's thesis, we investigate the work of poems construction based on the tension between the categories, in addition to the fragmentation. We could note that this tension leads the poetic speech into the silence, the death and the empty transcendence of the poetic word. The study of Orides Fontela's critical resource was made to carry out this research. Barbosa's (1986), Friedrich's (1991) and Valery's (1999) theories were used to discuss the positive and negative categories, and Steiner's (1988) and Friedrich's (1991), contributed for the analysis of silence